The Chilean Feminist May of 2018 on the Crest of the Fourth Wave. Use and Appropriation of Social Networks - Sola-Morales, S (UNIV CHILE, FAC CIENCIAS SOCIALES, 2021)
This article explores the processes of appropriation of social networks by the Chilean feminist movement in May 2018. There has been a virtual ethnography and participant observation of the digital initiatives carried out by the most relevant actors of the movement: the students, the organizations and parliamentarians of the Kirkwood bench. Specifically, the use of the main online platforms (Facebook and Twitter) was explored and their role in the protests was questioned in relation to three axes: a) proposed gender identity, b) slogans and dissemination of political ideas and c) functions of the networks social. The main conclusion reached was that the networks had an important informative role, as alternative sources to the discourse of the hegemonic media, expanding and making feminist issues visible in the public sphere and favoring the interaction between different voices. There is a predominance of an inclusive identity, which incorporates unity in difference, and a multiplicity of slogans, which shows the expansion of the new feminist political subject of the fourth wave: plural and diverse.